ANAISIS PENGARUH SERVICE QUALITY DAN COMPLAIN HANDLING TERHADAP CUSTOMER SATIFICATION PADA NITE AND DAY HOTEL MELAWI: ANAISIS PENGARUH SERVICE QUALITY DAN COMPLAIN HANDLING TERHADAP CUSTOMER SATIFICATION PADA NITE AND DAY HOTEL MELAWI - Venny Adhita Octaviani; Imam Asrori (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
Abstract: This research was conducted to analyze the influence of service quality and complaint handling on customer satisfaction with a sample of 91 Melawi Hotel Nite and Day consumers. The research results show that partially service quality has no significant effect on customer satisfaction (sig t count > 0.05). Furthermore, complaint handling has a significant effect on customer satisfaction (sig t < 0.05). The results of the F test showed that service quality and complaint handling together (simultaneously) influenced customer satisfaction at the Nite and Day Hotel Melawi, indicated by the calculated F significance value <0.05